A study into wellbeing, student engagement and resilience in early-adolescent international school students. (April 2021) - McKeering, Phillipa; Hwang, Yoon-Suk; Ng, Clarence
Growth in the international school sector continues, with significant expansion of the sector in Asia. Whilst substantial research has been conducted on the adjustment experience of tertiary-aged students, limited research attention has been given to school-aged students in international schools. The environment, conditions and challenges experienced by school-aged international students can differ considerably from those of tertiary-aged international students. This can be heightened during early-adolescence with adjustment from school mobility linked to many negative developmental outcomes. The present study investigates wellbeing, engagement and resilience of 178 early-adolescent international school students (aged 10-14) from an international school in Singapore that offers the International Baccalaureate Diploma and the national curriculum of England. Results reported a positive significant association between wellbeing, engagement and resilience constructs. The study also identified demographic and mobility characteristics that were associated with lower levels of wellbeing, behavioural engagement and resilience. Findings of the study highlight a potential cohort of early-adolescent international students who could benefit from additional support.